Pelaksanaan Ekstrakurikuler Seni Tari di MTsN 7 Pesisir Selatan - Marriyel Jelly Fahmi; Darmawati Darmawati (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
The purpose of this study is to increase students' interest in the implementation of dance extracurricular activities at MTsN 7 Pesisir Selatan. This type of research is qualitative research with a descriptive analysis approach. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data collection techniques are carried out by means of literature studies, observations, interviews, and documentation. The steps to analyze data are data collection, data reduction, data presentation and conclusion drawn. Dance extracurricular activities are carried out in stages, starting with gathering students who are interested in participating in dance extracurricular activities, making schedules, and providing materials. Dance extracurricular activities began with the recruitment of new members, students who were interested in participating in dance extracurricular activities totaling 20 people. After carrying out extracurricular activities in dance with umbrella dance learning, students' interest began to increase, this can be seen from the enthusiasm of students who attended every meeting. Then from the learning carried out by 8 students who were able to perform dance movements with a good level of memorization, 10 students who lacked memorization and 2 students who had difficulty practicing the dance movements given by the coach during dance extracurricular activities with limited facilities and inadequate infrastructure.